Time calibration for the end cap TOF system of BESⅢtime-of-flight detector, oiYline calibration, time resolution - 赵川 孙胜森 李澄 张晓杰 何康林 安琪 陈宏芳 代洪亮 封常青 衡月昆 黄亚齐 黄燕萍 郭建华 李卫东 李秀荣 刘芳 刘怀民 刘树彬 刘曙东 刘勇 马想 毛泽普 邵明 孙勇杰 孙志嘉 吴金杰 杨桂安 赵雷 朱兴旺 左嘉旭 (Chinese physics C, 2011)
The time calibration for end cap TOF system of BESIII is studied in this paper. It has achieved about 110 ps time resolution for muons in dimu events. The pulse height correction using electronic scan curve and the predicted time calculated using Kalman filter method are introduced. This paper also describes the study of using electrons and muons as calibration samples.